Urban model and jesuit schools in America - Jaliri Castellon, María (2024)
The evangelizing mission of the Jesuits in America was embodied in urban and architectural facts. The Jesuit urban complexes were made up of 1 or more apple trees with three fundamental functions: evangelizing, educational, and residential, which were complemented by cultivation and storage. The reflection and analysis of these Jesuit groups was carried out through a comparative consideration in the American context: the case of Cuzco - Peru, Cordoba - Argentina and the block of Villa de La Plata today Sucre Bolivia. These urban complexes have a common denominator: their basic functions: evangelizing, educational and residential, translated into churches, schools, seminaries and residences; evidencing that the residential and educational function is arranged around courtyards in the form of cloisters, the evangelizing function in churches is usually of a Latin cross plan and is complemented by orchards, pharmacies, warehouses and others in such a way that their daily activity allows them to develop fully. These American examples highlight the particular presence of the Indian chapel, which in the vast majority of case studies lacks physical and documentary evidence, remaining a pending issue to be investigated.